Cost Estimation of First-Line Antiretroviral Therapy with Zidovudine/Stavudine as the Nucleoside Backbone in India: A Pilot Study. (March 2015) - Thuppal, Sowmyanarayanan V.; Karthik, Rajiv; Abraham, Ooriapadical C.; Wanke, Christine A.; Mwamburi, Mkaya; Terrin, Norma; Cohen, Joshua T.; Mathai, Dilip; Muliyil, Jayaprakash; Kang, Gagandeep
Background: In India, a zidovudine-based regimen is preferred as the first-line drug treatment for HIV, despite high rates of drug toxicity. This study estimates the treatment costs for HIV. Methods: Eligible patients were enrolled from Antiretroviral Therapy Center, Christian Medical College, India. Baseline demographic and clinical characteristics, medical and nonmedical expenditure, and lost income were collected. Results: Of 41 patients enrolled and followed for 6 months, HIV treatment toxicity and opportunistic infections were reported by 12 (29%) and 13 (31.7%) patients, respectively. The median total costs, direct costs, and out-of-pocket expenditure were Indian rupees (INR) 9418 (US181), 8727 (US168), and 7157 (US138), respectively. Diagnostic tests accounted for 58% of the expenses. HIV treatment accounted for 34% of the median income earned INR 21 000 (US404). Expenditure for treatment with toxicity was 44% higher than without toxicity. Conclusion: Current treatment is associated with toxicity, increasing treatment costs and imposing a significant economic burden.